2016
DOI: 10.1016/j.ygyno.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of comprehensive genomic profiling to direct point-of-care management of patients with gynecologic cancers

Abstract: OBJECTIVE To determine the feasibility and clinical utility of using comprehensive genomic profiling (CGP) in the course of clinical care to identify clinically relevant tumor genomic alterations for patients with either rare or refractory gynecologic cancers to facilitate point-of-care management. Use of an expert, multidisciplinary, institutional molecular tumor board (MTB) assessment is discussed regarding input on putative targeted options for individualized therapy. METHODS A prospective clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…Notable exceptions were higher HRD scores associated with better clinical outcomes in GBM and OV ( Figure 3C ), and with overall survival in OV ( Figures S7B and S7C ). This may reflect the use of potent, DNA-damaging platinum-based compounds as standard-of-care therapy for OV ( Figure S7 ) ( Mills et al, 2016 ). The association of a higher HRD score with better outcomes in GBM may be linked to IDH mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Notable exceptions were higher HRD scores associated with better clinical outcomes in GBM and OV ( Figure 3C ), and with overall survival in OV ( Figures S7B and S7C ). This may reflect the use of potent, DNA-damaging platinum-based compounds as standard-of-care therapy for OV ( Figure S7 ) ( Mills et al, 2016 ). The association of a higher HRD score with better outcomes in GBM may be linked to IDH mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Although standard MSI testing captures the nearly 28% of endometrial cancers that are MSI‐H, patients with high TMB and MSS tumors because of POLE ‐mediated mechanisms (7%) and others go undetected , and thus potentially relevant treatment options remain unexplored. A recent analysis suggests that genomic profiling aids in clinical decision‐making in gynecologic cancers .…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…The authors concluded that broad implementation of multiplex hotspot testing is feasible but that only a small portion of the patients with cancer characterized by actionable alterations were actually enrolled onto genotype-matched trials. Other studies on smaller populations have provided support for the ability of comprehensive tumor genomic profiling to direct the point-of-care management of patients with cancer, (10,11) although the percentage of patients subsequently enrolled in genotype-matched clinical trials was similarly low (10).…”
Section: Current Approachesmentioning
confidence: 99%
“…To increase the number of feasible therapeutic options recommended for patients undergoing broad-based genomic sequencing, many center-wide efforts have been initiated (9)(10)(11)(12)(13). These often recommendations to the referring physician in a point-of-care manner, and subsequent follow up of patient outcomes.…”
Section: Current Approachesmentioning
confidence: 99%
See 1 more Smart Citation